THE MOVEMENT OF STRUGGLING OF NEO-COMMUNISM RISING IN POST-REFORM (A Study of Ideology and Struggle Movement in Indonesia) - Ahmad Suhaimi; Pagar Pagar (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
The trauma of the nation's children has not been able to recover from the betrayal many times for the same cause by the PKI. The events of Madiun in 1948, and G.30S PKI became menumental witnesses of the martyrdom of thousands of scholars and students of PKI's savagery, as well as the death of the nation's heroes because they were kidnapped, slaughtered, sliced and dragged into crocodile holes. The reform era, which tends to care about human rights, democratization, and freedom of thought, expression and opinion, has been misused for the growth and re-emergence of communism in Indonesia. Thus the research was proposed: "The Post-Reformation Neo-Communism Struggle Movement. (Study of Ideology and Struggle Movement in Indonesia). This research is specifically to discuss Neo-Communism and its relation to the possibility of a revival in Indonesia. The problem formulation is the movement for the struggle for the rise of Neo-Communism after Reformation in Indonesia, especially from the ideological aspects and the struggle movement. This type of research is qualitative and presented in descriptive exposures. Regional sample; North Sumatra, Aceh, DKI and West Java. Research findings; "Neo-Communism in Indonesia has emerged despite a small movement.  Keywords; Neo-Communism, Movement, internalization, religion.